L'intarsio nei marmi ravennati della tarda Antichità e dell’alto Medioevo (Fenestella. Inside Medieval Art, 2025)
This contribution aims to investigate the little-known aspect of the presence in Ravenna of marble materials of Byzantine workmanship or local production. Specifically, an analysis of some inlaid furnishings is proposed. Here I would like to take a closer look at the subject of working the surface of marble through the insertion of polychronous rocks or metal materials, which in Ravenna mainly took the form of enriching the proconnesio furnishings with grafts of various kinds. This technique was part of the wide range of practices implemented to add colour, typical of those years.
Keywords: Ravenna; Marmo; Edilizia di culto; Arredi liturgici; Arredi architettonici